2010
DOI: 10.1029/2009ja014543
|View full text |Cite
|
Sign up to set email alerts
|

Sprite initiation altitude measured by triangulation

Abstract: [1] High time resolution (10,000 frames per second) images of sprites combined with multistation concurrent video recordings have provided data for triangulation of the altitude of the initial sprite onset. The high-speed images were obtained from the Langmuir Laboratory, New Mexico, during summer campaigns in 2007 and 2008 with video observations from sites at Portales, New Mexico, and Las Vegas, New Mexico. Sprites start with one or more downward-propagating streamer heads. The triangulated onset altitudes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
60
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 37 publications
11
60
0
Order By: Relevance
“…4b may be the upward streamers that lead to the observed carrot sprites, in good agreement with the results reported by Stenbaek-Nielsen et al (2010) in which downward streamers create C type sprites (namely, columniform sprites, characterized by bright vertical columns in video imagery), while the upward streamers form the broad diffuse tops of carrot sprites. It should be noted that the bottom and top altitudes of sprites in this study may be underestimated to some extent because of clouds in the camera field of view.…”
Section: Characteristics Of the Sprite Imagessupporting
confidence: 78%
See 1 more Smart Citation
“…4b may be the upward streamers that lead to the observed carrot sprites, in good agreement with the results reported by Stenbaek-Nielsen et al (2010) in which downward streamers create C type sprites (namely, columniform sprites, characterized by bright vertical columns in video imagery), while the upward streamers form the broad diffuse tops of carrot sprites. It should be noted that the bottom and top altitudes of sprites in this study may be underestimated to some extent because of clouds in the camera field of view.…”
Section: Characteristics Of the Sprite Imagessupporting
confidence: 78%
“…4b) shows that it mainly developed upward. High-speed images reported by Stenbaek-Nielsen et al (2010) showed that sprites start with downward-propagating streamer heads at altitudes varying between 66 and 89 km, and in some cases the downward streamers are followed later by upward streamers starting from a lower altitude varying from 64 -78 km.…”
Section: Characteristics Of the Sprite Imagesmentioning
confidence: 99%
“…This conclusion is also consistent with the result from a recent analysis of high-speed images obtained with one of the most sensitive cameras currently in use in sprite observation. For streamers emerging out of a dark background, the analysis has indicated that the first detected streamer heads likely have already propagated a few kilometres 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, only the bottom half simulation region is shown for the optical emissions, because there are no visible emissions above. The intensity of the glow at 6 ms before streamer initiation is much weaker than the streamer head at 6.55 ms that has propagated more than 1 km distance, which is likely to be the first streamer head detected by intensified, high-speed cameras 29 . The intensity of the preceding glow is therefore below the detection limit of the current sprite observation systems, and this streamer will appear to emerge from a dark background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation